Answer:
B.
Step-by-step explanation:
When reflecting over the x-axis:
(x, y) (x, -y)
The y changes signs (+, -)
12/24 simplifies to 1/2, seeing as 12 is half of 24. :) Your answer is C.
As an opportunity to respond to people who might disagree with your claim.
Answer:
x = 6 2/3
Step-by-step explanation:
10+3(x+2)=36
10+3x+6=36 Solve inside the parenthesis.
16+3x=36 Combine like terms.
-16 -16 Subtract 16 from both sides.
3x/3=20/3 Divide both sides by 3.
x=6 2/3 The answer is x= 6 2/3, or 6.66666666666667
<u>We are given the equation:</u>
(a + b)! = a! + b!
<u>Testing the given equation</u>
In order to test it, we will let: a = 2 and b = 3
So, we can rewrite the equation as:
(2+3)! = 2! + 3!
5! = 2! + 3!
<em>We know that (5! = 120) , (2! = 2) and (3! = 6):</em>
120 = 2 + 6
We can see that LHS ≠ RHS,
So, we can say that the given equation is incorrect